MANAGEMENT MECHANISMS OF ENTERPRISES: ADOPTING AGILE MANAGEMENT PRINCIPLES IN TRADITIONAL INDUSTRIES - Nabiev Bobur Muhammadkosim ogli (TADQIQOTLAR.UZ, 2024)
Abstract:Management mechanisms are foundational frameworks and practices within organizations that facilitate effective leadership, operational efficiency, and strategic alignment. These mechanisms encompass a spectrum of approaches, ranging from traditional hierarchical structures and centralized decision-making to modern agile methodologies and decentralized, collaborative frameworks. Key components include organizational culture, leadership styles, strategic planning processes, performance measurement systems, and adaptation to technological advancements. The evolution of management mechanisms reflects ongoing efforts to optimize productivity, enhance employee engagement, navigate market complexities, and sustain long-term growth. By implementing appropriate management mechanisms tailored to organizational needs and external dynamics, businesses can adapt, innovate, and thrive in today's competitive landscape.